Vitamin A deficiency in Brazilian Children younger than 5 years old: a systematic review - Dixis Figueroa Pedraza (Instituto Materno Infantil de Pernambuco, 2020)
Abstract Objectives: to examine the nutritional status of vitamin A in Brazilian children under 5 years old, delimiting their deficiency and associated factors. Methods: this is a systematic review of articles published between 2008 and 2018, using the SciELO, Bireme, and PubMed electronic databases. A validated instrument critically evaluated the studies. The summary measures were obtained by the random effect model, and their results are presented using the Forest Plot graph. The qualitative synthesis was based on the description of the main factors associated with Vitamin A Deficiency. Results: we included 14 cross-sectional studies with observations in basic health units, daycare centers, and households. The summary measure indicated Vitamin A Deficiency of 20% (CI95%= 17% - 23%), with high homogeneity according to the source of the sample. Lower age of the child, low birth weight, poor iron nutritional status, diarrhea, subclinical infection, inadequate basic sanitation conditions, younger mothers and less maternal educa-tion represented the main exposures associated with the outcome. Conclusion: the results show Vitamin A Deficiency as a public health problem in Brazilian children under 5 years old, especially when related to the development of infectious processes and maternal and child characteristics that show greater susceptibility.